On the Pass-Through of Large Devaluations - Carlos Casacuberta; Omar Licandro (Center for Economic Studies and ifo Institute (CESifo), 2023)
In 2002 Uruguay faced a sudden stop of international capital flows, inducing a deep financial crisis and a large devaluation of the peso. The real exchange rate depreciated and exports expanded. Paradoxically, export shares and real exchange rates negatively correlate among Uruguayan exporters around 2002. To unravel this paradox, we develop a small open economy model of heterogeneous firms. Domestic firms are price takers in the international market, operate under monopolistic competition in the domestic market, and face financial constraints when exporting. Confronted to a large nominal devaluation, financial constraints deepen. Financially constrained exporters cannot optimally expand in the export market and react by passing-through the devaluation to the domestic price only partially, expanding domestic sales. As a consequence, the more financially constrained exporters are, the less their export shares expand and the more their firm specific real exchange rates depreciate. As a result, export shares and real exchange rates of exporters are negatively correlated as in the data.
Keywords: 330